2002
DOI: 10.1002/cncr.10257
|View full text |Cite
|
Sign up to set email alerts
|

Combined chemotherapy and radiation therapy for head and neck malignancies

Abstract: Acute side effects of combined chemotherapy and radiation therapy usually were found to resolve after treatment. Long-term morbidity is substantial because of xerostomia and severe dysphagia. However, preliminary studies suggest that because of organ preservation, patients may achieve a better quality of life after chemoradiation compared with the conventional use of surgery and postoperative radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
170
1
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(188 citation statements)
references
References 77 publications
10
170
1
7
Order By: Relevance
“…[1][2][3] If a less than-desired dose is used to reduce damage to healthy tissues, it may result in diminished quality of life and higher morbidity rate for these individuals. 3 In radiation therapy for head and neck cancer, the major salivary glands often receive a high radiation dose. Acute and chronic responses displayed by salivary glands after radiation are related to dose of radiation and the amount of the glands in the direct line of the beam.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] If a less than-desired dose is used to reduce damage to healthy tissues, it may result in diminished quality of life and higher morbidity rate for these individuals. 3 In radiation therapy for head and neck cancer, the major salivary glands often receive a high radiation dose. Acute and chronic responses displayed by salivary glands after radiation are related to dose of radiation and the amount of the glands in the direct line of the beam.…”
Section: Introductionmentioning
confidence: 99%
“…The EORTC QLQ-H&N35 is widely used to measure quality of life in H&N cancer patients (Singer et al, 2013). Both prospective and cross-sectional studies (Bjordal et al, 2001;Hammerlid et al, 2001aHammerlid et al, , 2001bHammerlid et al, , 2001cNguyen et al, 2002;Talmi et al, 2002;Shepherd and Fisher, 2004) have documented reductions in HRQOL in populations of H&N cancer patients who have received RT. Several studies have also examined changes in HRQOL during the treatment period (Bjordal et al, 2001;Henson et al, 2001; Airolldi et al, 2004;Parliament et al, 2004;Jabbari et al, 2005; Braam et al, 2007; Curran et al, 2007; Ackerstaff et al, 2009; Ackerstaff et al, 2012;Maguire et al, 2011;Maurer et al, 2011;Nutting et al, 2011).…”
mentioning
confidence: 99%
“…These treatments therefore have the potential to substantially diminish QoL and may cause many patients to prematurely stop taking medication, resulting in treatment failure. 46,47 A QoL analysis of a phase III trial comparing high-dose radiotherapy with or without concomitant cetuximab 48 concluded that the addition of cetuximab to radiotherapy significantly improved locoregional control and increased overall survival without having any significant effects on QoL. In this study, compliance with completing QoL questionnaires was high and the data are therefore considered to be reliable.…”
Section: Quality Of Lifementioning
confidence: 84%